Brain-gut axis: From the conditioned reflex to the microbiota-gut-brain communication system - Klara Gyires (Интегративная физиология, 2020)
Communication between the central nervous system (CNS) and the gastrointestinal tract is called the brain-gut axis. This communication network includes the CNS, hypothalamic-pituitary-adrenal axis, the autonomic nervous system (sympathetic and parasympathetic), the enteric nervous system and the gut microbiota. From the conditioned reflex activity in gastric acid secretion discovered by Pavlov to the recognition of the role of CNS in stress-induced gastric ulcer and exacerbation of intestinal inflammation, all these facts confirm the significance of brain-gut axis. Moreover, mental illnesses and depression also result in high risk for developing subsequent gastrointestinal mucosal injury. The brain-gut axis is bidirectional; therefore, not only the CNS affects the gastrointestinal functions, but the gut information is also forwarded to the CNS, which may modify its activity. Several observations suggested that changes in microbiome composition can be manifested in alterations of behavior and cognition; and a strong correlation between dysbiosis and psychiatric disorders has been observed. These observations substantially contributed to the establishment of the concept of the microbiota-gut-brain axis. The present work aims to overview the mutual role of brain-gut-microbiota and microbiota-gut-brain axis in the development of gastrointestinal and mental disorders as well as their mechanisms.